Clinical inertia in the pharmacological management of hypertension: A systematic review and meta-analysis. Issue 25 (June 2018) - Milman, Tal; Joundi, Raed A.; Alotaibi, Naif M.; Saposnik, Gustavo
Abstract: Background: Clinical Inertia is defined as "failure of health care providers to initiate or intensify therapy according to current guidelines". This phenomenon is gaining increasing attention as a major cause of clinicians' failure to adequately manage hypertension, thus leading to an increased incidence of cardiovascular events. We performed a systematic review and meta-analysis of randomized controlled trials to determine whether interventions aimed at reducing clinical inertia in the pharmacological treatment of hypertension improve blood pressure (BP) control. Methods: MEDLINE, Embase, and Cochrane Database of Systematic Reviews were searched from the start of their database until October 3, 2017 for the MESH terms "Hypertension" or "Blood Pressure", their subheadings, and the keywords "Therapeutic Inertia" or "Clinical Inertia". Studies were included if they addressed pharmacologic hypertension management, clinical inertia, were randomized controlled trials, reported an outcome describing prescriber behavior, and were available in English. Data for the included studies was extracted by two independent observers. Quality of studies was analyzed using the Cochrane Risk of Bias Assessment. Data was pooled for statistical analysis using both fixed- and random-effects models. The primary study outcome was the percentage of patients achieving blood pressure control as defined by the Joint National Committee guidelines or study authors. Results: Of 474 citations identified, ten met inclusion criteria comprising a total of 26, 871 patients, and eight were selected for meta-analysis. Interventions included Physician Education, Physician Reminders, Patient Education, Patient Reminders, Ambulatory BP Monitoring, Digital Medication Offerings, Physician Peer Visits, and Pharmacist-led Counselling. Pooled event rates revealed more patients with controlled BP in the intervention group versus control (55%, 95% CI 46-63% versus 45%, 95% CI 37-53%) and interventions significantly improved the odds of BP control (OR = 1.19, 95% CI = 1.12−1.27, P  < .001). Heterogeneity in the quantitative analysis was moderate. Conclusions & Relevance: Addressing clinical inertia through physician reminders, ambulatory BP monitoring, and educational interventions for primary care providers was associated with an improvement in blood pressure control. Our findings encourage further research to investigate strategies at reducing clinical inertia in the management of hypertension. Abstract : Supplemental Digital Content is available in the text